A new dynamic SOH estimation of lead‐acid battery for substation application. (26th September 2016) - Liu, Xintian; Yang, Yafei; He, Yao; Zhang, Jiangfeng; Zheng, Xinxin; Ma, Mingyao; Zeng, Guojian
Summary: State of Health (SOH) is one of the most important parameters of lead‐acid batteries. Most of the existing SOH estimation methods only take the influence of charge cycles into consideration, and the estimation accuracy is limited. Batteries in the substations have two typical states: one is the check‐discharge state, in which the batteries are discharged for 8 h at 0.1 C (Capacity) to determine whether the battery pack has certain reliability. The other is the floating charge state, in which the batteries are connected to the charger to maintain full power. This paper proposes a novel SOH estimation method based on the two states. In the check‐discharge state, the relationship between the voltage and the age of battery is analysed. The health index, which is introduced in this model, is affected by the age of battery. In the floating state, the relationship between the internal resistance and the age of battery is discussed. Another SOH model is established based on the change of the internal resistance. By combining the two models, the estimation method can achieve real‐time estimation and high accuracy for substation application. An accelerated life test is applied to verify the theoretical analysis. The experimental results demonstrate that the SOH estimation error is less than 3% which is very satisfactory for practical applications. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This paper proposes a novel State of Health estimation method based on two states. The method is suitable for lead‐acid battery for substation application. It can achieve high accuracy which is demonstrated by experiment.